FINANCIAL LITERACY AS A TOOL FOR CRISIS PREVENTION - Maksudkhojaeva Dilshodakhon Mansurkhoja kizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This paper examines the impact of financial literacy on a country's economic development and its relationship with GDP growth. Particular attention is paid to the consequences of the global financial and economic crisis of 2008.